2024
DOI: 10.1136/jcp-2023-209269
|View full text |Cite
|
Sign up to set email alerts
|

Morphology combined withHER2D-DISH ploidy analysis to diagnose partial hydatidiform mole: an evaluation audit using molecular genotyping

Caroline M Joyce,
Geoffrey J Maher,
Susan Dineen
et al.

Abstract: AimsA hydatidiform mole (HM) is classified as complete (CHM) or partial (PHM) based on its morphology and genomic composition. Ancillary techniques are often required to confirm a morphologically suspected PHM diagnosis. This study sought to evaluate the clinical accuracy of PHM diagnosis using morphological assessment supported byHER2dual-colour dual-hapten in situ hybridisation (D-DISH) ploidy determination.MethodsOver a 2-year period, our unit examined 1265 products of conception (POCs) from which 103 atypi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…HER2 DDISH ploidy assay did not overdiagnose PHM when audited by molecular genotyping. 23 In terms of a population bias accounting for differences in incidence rates, we did not observe births to younger mothers in Ireland where the average maternal age was 32.5 years compared with the European average (30.6 years). In terms of ethnicity, the majority of babies (77%) were born to mothers of Irish nationality.…”
Section: Original Researchmentioning
confidence: 54%
“…HER2 DDISH ploidy assay did not overdiagnose PHM when audited by molecular genotyping. 23 In terms of a population bias accounting for differences in incidence rates, we did not observe births to younger mothers in Ireland where the average maternal age was 32.5 years compared with the European average (30.6 years). In terms of ethnicity, the majority of babies (77%) were born to mothers of Irish nationality.…”
Section: Original Researchmentioning
confidence: 54%
“…This audit achieved 100% sensitivity and specificity (95% CI: ≥92%, n=36) confirming the accuracy of our novel scoring system. 22 It is important to note that ploidy analysis, while valuable in distinguishing diploid from triploid conceptuses, does not identify the genomic origin of the additional chromosomal complement in a triploid conceptus. This raises concerns about the potential overdiagnosis of PHM based on ploidy alone, as there is a risk of mistakenly including digynic triploid conceptuses.…”
Section: Original Researchmentioning
confidence: 99%
“…9 However, recent auditing of our service using molecular genotyping demonstrated that HER2 D-DISH ploidy analysis did not lead to misdiagnosing PHM due to digynic triploidy. 22 This suggests that, from a practical viewpoint, laboratories using morphological assessment supported by an accessible ploidy assay may (a) accurately exclude PHM by confirming diploid conceptus status and (b) confirm triploid status in suspected PHM cases without a substantial risk of overdiagnosis by miscategorising digynic triploid conceptuses.…”
Section: Original Researchmentioning
confidence: 99%